2016
DOI: 10.1098/rstb.2016.0009
|View full text |Cite
|
Sign up to set email alerts
|

Affective touch and attachment style modulate pain: a laser-evoked potentials study

Abstract: Affective touch and cutaneous pain are two sub-modalities of interoception with contrasting affective qualities (pleasantness/unpleasantness) and social meanings (care/harm), yet their direct relationship has not been investigated. In 50 women, taking into account individual attachment styles, we assessed the role of affective touch and particularly the contribution of the C tactile (CT) system in subjective and electrophysiological responses to noxious skin stimulation, namely N1 and N2-P2 laser-evoked potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
101
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(109 citation statements)
references
References 58 publications
7
101
1
Order By: Relevance
“…Furthermore, it may be possible to explore the role of CTs in pain and enhance pleasure in touch, without impacting on normal nociceptive functioning. This has implications for the function of CTs in pathologies, where they are proposed to contribute to mechanical (Liljencrantz et al, 2013; Nagi et al 2011) and cold (Samour et al 2015) allodynia, as well as understanding their role in gating pain (Krahé et al 2016; Liljencrantz et al 2014). The propensity of some low-threshold CMs to fire in response to gentle mechanical stimulation must be considered in future human behavioral and brain imaging studies, especially in pathological situations where response properties may be altered.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it may be possible to explore the role of CTs in pain and enhance pleasure in touch, without impacting on normal nociceptive functioning. This has implications for the function of CTs in pathologies, where they are proposed to contribute to mechanical (Liljencrantz et al, 2013; Nagi et al 2011) and cold (Samour et al 2015) allodynia, as well as understanding their role in gating pain (Krahé et al 2016; Liljencrantz et al 2014). The propensity of some low-threshold CMs to fire in response to gentle mechanical stimulation must be considered in future human behavioral and brain imaging studies, especially in pathological situations where response properties may be altered.…”
Section: Discussionmentioning
confidence: 99%
“…In experimental studies, it is well established that social support can modulate psychological and neurophysiological response to pain, in adults and in children (see Decety & Fotopoulou, 2015;Krahé et al, 2013, for reviews). Moreover, in experimental and neuroimaging studies with adults, we (AF's lab) have shown that this pain modulation depends on particular 'embodied' social support variables (e.g., the presence of another individual, affective touch by another individual), as well as individual differences in the perception of social relationships themselves, namely attachment styles (Hurter et al, 2014;Krahé et al, 2015;Sambo et al, 2013;Krahé et al, 2016). Insecure attachment styles in particular (characterised by negative expectations of social support), which may be linked with an impoverished oxytocin system (see Uvnäs-Moberg, Handlin, & Petersson, 2014), seem to moderate the relation between social support and pain (see also Meredith, 2013).…”
Section: The Affectively Touched Self: Learning Bodily Pleasure and Pmentioning
confidence: 98%
“…Insecure attachment styles in particular (characterised by negative expectations of social support), which may be linked with an impoverished oxytocin system (see Uvnäs-Moberg, Handlin, & Petersson, 2014), seem to moderate the relation between social support and pain (see also Meredith, 2013). Higher attachment anxiety (associated with seeking and craving signs of reassurance) led to reduced pain in the presence of a high vs. low empathic stranger (Sambo et al, 2013) and to reduced pain when receiving CT-optimal, affective touch (Krahé et al, 2016), while higher attachment avoidance (associated with distancing from others and preferring to cope alone) led to increased pain in the presence of a stranger (Sambo et al, 2013) or one's romantic partner and when receiving affective touch (Krahé et al, 2016).…”
Section: The Affectively Touched Self: Learning Bodily Pleasure and Pmentioning
confidence: 99%
“…Krahé et al [22] explore a boundary of interoception: the perception of affective touch conveyed by unmyelinated C-fibres. Such sensation is encompassed within Craig's broadened model of interoception, a view supported both by their anatomical organization through laminar 1 spinothalamic tract and by clinical observations [23].…”
Section: Interoception and Affectmentioning
confidence: 99%